Pengaruh Identifikasi dan Mitigasi Risiko Terhadap Penerapan Manajemen Risiko dan Maturitas pada Pabrik Pupuk dengan Internal Audit Sebagai Pemoderasi - Susilo, Budi - (Jurnal Riset Perbankan Manajemen dan Akuntansi, 2024)
The aim of the research is to examine the effect of risk identification and mitigation on the implementation of risk management and maturity with internal audit moderation at Fertilizer Company. This study uses primary data with a questionnaire with respondents employees of Fertilizer Company. with job levels Assistant Vice President, Vice President to Senior Vice President. The data analysis method used is a quantitative method based on Partial Least Square (PLS) Structural Equation Modeling (SEM) approach. The results of the research show that risk identification and risk mitigation have a positive and significant relationship to the implementation of risk management. Risk identification and risk mitigation have a positive and significant relationship to risk maturity. Internal audit moderates the relationship between risk identification and risk mitigation on the implementation of risk management. Besides that, the internal audit also moderates the relationship between risk identification and risk mitigation on risk maturity. Keywords: Risk Identification, Risk Mitigation, Risk Management, Internal Audit, Moderation